2008
DOI: 10.1152/japplphysiol.01307.2007
|View full text |Cite
|
Sign up to set email alerts
|

The airway response to deep inspirations decreases with COPD severity and is associated with airway distensibility assessed by computed tomography

Abstract: In patients with mild chronic obstructive pulmonary disease (COPD), the effect of deep inspirations (DIs) to reverse methacholine-induced bronchoconstriction is largely attenuated. In this study, we tested the hypothesis that the effectiveness of DI is reduced with increasing disease severity and that this is associated with a reduction in the ability of DI to distend the airways. Fifteen subjects [Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage I-II: n = 7; GOLD stage III-IV: n = 8] underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…As published previously, we believe that this decrease in distensibility is due to a combination of intrinsic remodeling of the airway walls and progressive parenchymal destruction. 11,15 We extended this knowledge by demonstrating that the association between emphysema and global airway distensibility remained after adjustment for relevant covariates, such age and sex. We believe that this adjustment is important because studies have shown differences in airway diameter changes with lung infl ation by sex and age in healthy lungs 24 and by age in diseased lungs.…”
Section: Airway Distensibility Across Groupsmentioning
confidence: 80%
See 1 more Smart Citation
“…As published previously, we believe that this decrease in distensibility is due to a combination of intrinsic remodeling of the airway walls and progressive parenchymal destruction. 11,15 We extended this knowledge by demonstrating that the association between emphysema and global airway distensibility remained after adjustment for relevant covariates, such age and sex. We believe that this adjustment is important because studies have shown differences in airway diameter changes with lung infl ation by sex and age in healthy lungs 24 and by age in diseased lungs.…”
Section: Airway Distensibility Across Groupsmentioning
confidence: 80%
“…It is known that the ability of the airways to dilate is attenuated in more severe stages of COPD. 10,11 We hypothesized that within a given disease stage, we would observe less dilation of the airways in the EP subtype than in the AP subtype. We refer to the airway caliber change with lung infl ation as airway distensibility.…”
Section: Ct Scan Examinationmentioning
confidence: 99%
“…25 The effect of lobar emphysema on the relationship between segmental Previously, we and other groups demonstrated that with increasing disease severity and increasing burdens of emphysema, airways become less distensible. 15,16 There may be several reasons for this observation, including mural fi brosis, which prevents dilation, and the disruption of the airway-parenchymal interdependence in emphysematous lungs, 15 which may reduce radial traction on the airway. 17 In either case, an incompletely expanded airway may appear to have an elevated WA% on CT scan that could be falsely attributed to a greater burden of airway disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dr Dransfi eld has received consultancy airway-parenchymal uncoupling suggested in prior investigations. 15,16 We and others have observed that reduced airway distensibility (change in airway caliber) with lung infl ation is associated with disease severity 16 and an emphysema-predominant COPD phenotype. 15 We extended these previous observations by demonstrating that airway dimensions are related to the burden of emphysema as measured by CT scan.…”
Section: Acknowledgmentsmentioning
confidence: 93%
“…Moreover, the luminal areas increased and wall thickness did not change in both bronchi, indicating that the improvement in WA% refl ects airway dilation, but not a decrease in wall thickness. Th ese changes were detected together with lung defl ation assessed as a decrease in CT-TLV, although previous studies using paired CT images at functional respiratory capacity and TLC showed that airway calibre can be increased with lung infl ation in healthy individuals and in many patients with COPD (35)(36)(37).…”
Section: Discussionmentioning
confidence: 91%